1)-6x- 13 = -7x - 14  2)5x = 8 + 3(2x + 3)  3)3(4x + 1) + 3x = 2x - 23 4)  7(2x - 5) - 4(5x + 3) = -33  5) 6x - 7(3x - 5) - 2(4x - 7) = 3  6) 12(x - 2) - (4x - 3) = 8(x + 3)  рещит​

shamshievoleg shamshievoleg    3   15.04.2019 19:03    2

Ответы
Lisska147 Lisska147  29.05.2020 13:49
1)
-6х-13=-7х-14
-6х-13+7х+14=0
-6х+7х=-14+13
х=-1
2)
5х =8+3(2х+3)
5х=8+6х+9
5х-8-6х-9=0
х-17=0
х=17
3)
3(4x + 1) + 3x = 2x - 23
12х+3+3х-2х+23=0
13х+26=0
13х=26
х=2
5)
6x - 7(3x - 5) - 2(4x - 7) = 3 
6х-21х+35-8х+14-3=0
-23х+46=0
х=-2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика